Falta de atención en el aula y bajo rendimiento escolar en los niños y niñas de educación inicial y primer año de educación general básica de la escuela fiscal mixta Juan Montalvo del cantón Pasaje en el periodo lectivo 2012-2013. - Barriga Fares, Cristina Alexandra (2013)
Le inattention is the most common learning disorder in childhood, it is also defined as the difficulty of the girl or the girl to keep the focus on homework or play activities. We can say that the lack of attention affects a lot in the teaching-learning process as it prevents the pupil to develop their cognitive and psychomotor skills.